Emergency Psychiatry before and during COVID-19 pandemia - A. Giménez-Palomo; M. Sagué; G. Fico; M. Gómez-Ramiro; M. Vázquez (European Psychiatry, 2022)
Introduction The COVID-19 pandemic had a significant impact worldwide. Consultations in the Emergency Service of the Hospital Clínic of Barcelona varied in terms of reasons for consultations, psychopathology, and other aspects, before and after the pandemic.